2004
DOI: 10.4219/jeg-2004-318
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of the Collaboration in Mathematics between a Fourth-Grade Teacher and a Talented and Gifted Coordinator

Abstract: The purpose of this case study was to describe how a 4th-grade teacher and a TAG coordinator collaborated to improve services for advanced learners without the support of university faculty and with limited resources. Interviews, questionnaires, transcriptions of videotaped consultation sessions, and observations of classroom instruction showed that participants coplanned lessons, utilized collaborative teaching, and developed a close rapport. Service was provided directly through a pull-out model that offered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Nevertheless, their report revealed that both gifted education teachers and general education teachers perceived they could more effectively teach students identified as gifted and enjoyed professional collaboration. Like other studies with consultation and co-teaching, time to co-plan was reported as a significant barrier (Kane & Henning, 2004; Scruggs et al, 2007).…”
Section: Is Collaboration Effective?mentioning
confidence: 72%
See 1 more Smart Citation
“…Nevertheless, their report revealed that both gifted education teachers and general education teachers perceived they could more effectively teach students identified as gifted and enjoyed professional collaboration. Like other studies with consultation and co-teaching, time to co-plan was reported as a significant barrier (Kane & Henning, 2004; Scruggs et al, 2007).…”
Section: Is Collaboration Effective?mentioning
confidence: 72%
“…Time for common planning should be built in the schedule, and this can be organized and supported at the administrative level. It has recommended that teachers co-plan for at least 30 min per week with set goals for sessions (Landrum, 2001; Kane & Henning, 2004). Furthermore, co-teaching would be more feasible if the district consistently implemented cluster grouping as in Masso (2004).…”
Section: Discussionmentioning
confidence: 99%
“…First, a short overview of the terms used in the articles is presented. All articles are about two or more teachers being responsible for every student's academic development in mathematics education; however, different terms are used for this collaboration: coteaching [35][36][37][38][39][40][41][42][43][44][45], cooperative teaching [46], collaborative teaching [47,48], and team teaching [49]. In the results, co-teaching is used, encompassing all the aforementioned terms.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies specify students' conditions as special needs or learning disabilities [35,37,44], students with disabilities [41,43,45], students with special educational needs (SEN) [38], or students having difficulties understanding the materials presented or solving problems [47]. In Kane and Henning [48], the participants were students who were advanced learners. The current review uses students in need of special education in mathematics (SEM) (cf.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation